DOI: 10.58530/2022/0957
|View full text |Cite
|
Sign up to set email alerts
|

Imaging near metal at 0.55 T using gradient-echo based sequences: Feasibility and Opportunities

Abstract: The large magnetic susceptibility difference between metallic implants and surrounding tissues causes severe MRI artifacts that scale with the B0 field strength. At conventional field strengths, spin-echo based multispectral imaging is used to mitigate this artifact and produce diagnostic images. At lower field strengths, such as 0.55 T, other strategies may be feasible. Here, we investigate gradient-echo based sequences for imaging near metal at 0.55 T, which provide high SNR efficiency and different contrast. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…127 As expected, they observed smaller and less disruptive image artifacts at 0.55 T for most devices, however, the amount of artifact reduction depends on the implant material. Keskin et al demonstrated the feasibility of gradient-echo-based sequences, including bSSFP, for near-metal imaging at 0.55 T. 128 Van Speybroeck et al demonstrated susceptibility artifacts for a 50 mT permanent magnet system in phantoms. 129 To date, few devices are labeled for low-field MRI.…”
Section: Imaging Patients With Implantsmentioning
confidence: 99%
“…127 As expected, they observed smaller and less disruptive image artifacts at 0.55 T for most devices, however, the amount of artifact reduction depends on the implant material. Keskin et al demonstrated the feasibility of gradient-echo-based sequences, including bSSFP, for near-metal imaging at 0.55 T. 128 Van Speybroeck et al demonstrated susceptibility artifacts for a 50 mT permanent magnet system in phantoms. 129 To date, few devices are labeled for low-field MRI.…”
Section: Imaging Patients With Implantsmentioning
confidence: 99%